Earlier presentation and application of curative treatments in hepatocellular carcinoma - Ulahannan, Susanna V. (2014)
PURPOSE: To assess the use of curative therapies for hepatocellular carcinomas (HCC) in the population. METHODS: HCC treatment patterns were examined in SEER 18 registries (28% of U.S.). Joinpoint regression analyses were performed to assess 2000–2010 incidence trends by tumor size, count and receipt of potentially curative treatments (transplantation, resection and ablation). SEER-Medicare data enabled evaluation of treatment patterns including receipt of sorafenib or TACE by HCC-associated co-morbidities. RESULTS: Diagnoses of tumors ≤5.0 cm in diameter significantly increased during 2000–2010, surpassing diagnosis of larger tumors. Overall, 23% of cases received potentially curative treatment. Joinpoint models indicated incidence rates of treatment with curative intent increased 17.6% per year during 2000–2005, then declined by −2.9% per year during 2005–2010 (P< 0.001). Among HCC cases with a single tumor ≤5.0 cm and no extension beyond the liver, use of ablative therapy significantly increased during 2000–2010. Use of invasive surgery for single tumors, regardless of size, significantly increased during the initial years of the decade then plateaued. The group most likely to receive curative treatment in the SEER-Medicare cases was patients with one, small tumor confined to the liver (657 of 1597 cases, 41%), with no difference in treatment by hepatic co-morbidity status (P=0.24). A higher proportion of cases with reported liver-associated co-morbidities were, however diagnosed with tumors ≤5.0 cm in diameter (1745 0f 2464, 71%) compared to patients with no reported co-morbidities (996 of 2596, 38%, P<0.001). CONCLUSION: Although more HCC patients were diagnosed with early disease over time, the use of curative treatments in this patient group has recently plateaued. Efforts to identify and treat more eligible candidates for curative therapy could be beneficial.